Internet Use Behaviour of European Tourists Towards the Decision of Traveling to Phuket Province - Poltanee , Issarapong; Boonphetkaew , Umaporn (Dusit Thani College Journal, 2020)
This study aimed 1) to study Internet Usage behavior of European tourists towards decision of travelling to Phuket province, and 2) to compare decision making behaviors of European tourists by to personal factors. The survey sample size had been determined by testing the questionnaire with the 40 samples and calculated Partial R2 to estimate the sample size using the G*Power program according to Cohen’s (1977). Based on sample estimation, the effect size is equal to 0.0683863 calculated from 40 samples. The probability of type I errors (α) is equal to 0.1 and number of variables predicted is equal to 10. Power of Test (1-ß) is equal to 0.95 (Cohen, 1962), creating sample size of 200 samples. Statistics used in data analysis are: Frequency, Percentage, Mean, and Standard Deviation (SD). Hypothesis testing was used to compare demographic differences by analyzing statistics through T-test and One - way ANOVA or F-test (analysis of variance). The results of this study showed that most foreign tourists taking a trip to Phuket were single male, age between 26 to 35 years old with Bachelor’s degree and their monthly income is 751 - 1,500 working as a company employee. From online media, their decision making behaviors in selecting Phuket as a travel destination, mostly came from the users’ (tourists’) ability to make decisions. Decision making in selecting Phuket as a travel destination also came from the quality of information provided by online travel media. Moreover, the online travel media information obviously helps tourists decide to travel to Phuket. The European tourists deciding to take a trip to Phuket with different genders, ages, levels of education, income and careers, however, make no difference regarding making decisions on travel.